Deconvolution Tactics and Normalization in Renal Spatial Transcriptomics - Melo Ferreira, Ricardo; Freije, Benjamin J.; Eadon, Michael T. (Frontiers in Physiology, 2022)
The kidney is composed of heterogenous groups of epithelial, endothelial, immune and stromal cells, all in close anatomic proximity. Spatial transcriptomic technologies allow the interrogation of in situ expression signatures in health and disease, overlaid upon a histologic image. However, some spatial gene expression platforms have not yet reached single cell resolution. As such, deconvolution of spatial transcriptomic spots is important to understand the proportion of cell signature arising from these varied cell types in each spot. This article reviews the various deconvolution strategies discussed in the 2021 Indiana O’Brien Center for Microscopy workshop. The unique features of Seurat transfer score methodology, SPOTlight, Robust Cell Type Decomposition, and BayesSpace are reviewed. The application of normalization and batch effect correction across spatial transcriptomic samples is also discussed.